The impact of financial integration on economic growth Case of Maghreb countries - KOUKI, Saoussen; REZGUI, Sami (Archives of Business Research, 2017)
The relationship between financial integration and economic growth is a vital subject. Many empirical and theoretical works showed that financial integration could help countries to increase their growth rate and ameliorate their life quality. The target of this work is to study financial integration effects of thirty-five years, from January 1981 until December 2014, on economic growth of the three Maghreb countries (Algeria, Morocco and Tunisia) using the ARDL approach to cointegration testing. Estimations results indicate that financial integration affects positively the economic growth of the Maghreb countries.